1957
DOI: 10.1139/b57-048
|View full text |Cite
|
Sign up to set email alerts
|

The Inheritance of Coumarin in Sweet Clover

Abstract: The inheritance of coumarin in white blossom sweet clover was determined from a study of crosses involving plants of the variety Arctic (containing free coumarin). Pioneer (containing bound coumarin), and coumarin-deficient selections. Both a flurometric and a colorimeter test were used to detect the presence and type of coumarin.Among high-coumarin plants, variation in the amount of coumarin was due to non-heritable causes or genetic factors not detected in this study. The cross of free-coumarin × bound-couma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1958
1958
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…The partial dominance of cu is in apparent disagreement with the results of other studies in which F2 ratios of three high-coumarin to one low-coumarin have been reported (3,9). This disagreement is readily understood when one considers that the £luorometric procedure for the detection of o-hydroxycinnamic acid is so sensitive that, in a qualitative test, the levels of o-hydroxycinnamic acid occurring in Cucu plants may be classified as high.…”
Section: Resultscontrasting
confidence: 99%
“…The partial dominance of cu is in apparent disagreement with the results of other studies in which F2 ratios of three high-coumarin to one low-coumarin have been reported (3,9). This disagreement is readily understood when one considers that the £luorometric procedure for the detection of o-hydroxycinnamic acid is so sensitive that, in a qualitative test, the levels of o-hydroxycinnamic acid occurring in Cucu plants may be classified as high.…”
Section: Resultscontrasting
confidence: 99%
“…Goplen et al . 44 studied the influence of two pairs of alleles, Cu/cu and B/b, upon the level and form of coumarin in M. albus . This study suggested that Cu/cu alleles determine high or low levels of coumarin and that the B/b alleles influence the form and type of coumarin 44 .…”
Section: Resultsmentioning
confidence: 99%
“…ulb« the lowcoumarin character of M. dentata. and genetic studies by Gorlen et al (2) demonstrated that this character is governed by a single pair of alleles, designated Culm. The ell gene is the basis for the low-coumarin varieties, Cumino and Denta.…”
Section: Occurrence Of O-hydroxycinnamic Acid In Species Ofmentioning
confidence: 99%